Effect of Initial Collar Diameter, Shoot Pruning and Root Pruning on Performance of Planting Stock of Celtis australis - Bhardwaj, S. D.; Panwar, Pankaj; Yadav, Vasu (Indian Forester, 2002)
The planting stock of Celtis australis having collar diameter (1.0 to 1.50 cm), shoot pruning (6 cm above collar) and no root pruning are recommended for better establishment of the seedlings in degraded tracts of mid hill zones of Himachal Pradesh.